Petty Cash Daily Report Input System at PT. Inti Indokomp - Widiyanti, Widiyanti (International Journal of Business and Information Technology, 2024)
Petty cash is called petty cash, a number of funds formed specifically for routine money are issued and the amount is relatively small. This cash is generally also used for the purpose of paying a small nominal. In outlining each transaction, the small cash statement provides an accurate picture of the company's liquidity, helping management make informed decisions to manage and optimize financial resources This study uses a secondary data source, a method of collecting data by means of observation. The object of this research is PT Inti Indokomp in Pekanbaru City PT Inti Indokomp in the implementation of the petty cash daily report input system using the general Ledger application. Where in the data input system is well organized and systematic